Reasons for Increasing the Number of Members of the Great Khural of Mongolia and Its Impact Over the Next 10 Years - Dagva-Ochir, Bumdari; Bayarmagnai, Bayarbaatar (Technium Social Sciences Journal, 2024)
During their term of office, members of parliament are responsible for passing laws, monitoring government activities, and approving the budget to ensure the legitimacy of parliament while representing the interests of citizens. However, in recent years, the ability of parliamentarians to effectively represent citizens has weakened, with growing concerns about their accountability and ethics. This highlights the need for a study on the negative impacts of these issues. The concept of the "optimal size of parliaments" explores the capacity of parliaments to fully perform their duties. The aim of this research is to determine the appropriate number of members for the Mongolian parliament, ensuring it remains at an optimal size. Specifically, the effectiveness of the parliament is linked to its size, as the ability to maintain ethical standards and properly implement laws that benefit society is connected to the number of representatives. The size of parliament affects its capacity to represent citizens, the workload it can manage, and its overall efficiency during the term of elected members. The research results suggest that the optimal number of members in the Mongolian parliament could range between 114, 151, and 155, considering factors such as traditions, geography, administrative divisions, and the electoral system. As a result of this study, the Constitution was amended in 2023 to increase the number of members to 126, which reflects the findings of this research.